Effect of Heat Treatment Temperature on the Microstructure, Wear and Friction of Ni-Nb-V Alloyed Manganese Steel - Ayadi, Souad; Hadji, Ali; Kaleli, Emrullah Hakan (SPRINGER INT PUBL AG, 2025)
The focus of this work is the effect of heat treatment temperature upon the microstructure, hardness, wear and friction of high manganese steel produced in an industrial setting. The obtained steels were subjected to two heat treatments, one at 1050 degrees C and the other at 1100 degrees C followed by water quenching. The microstructures were characterized by optical microscopy and scanning electron microscopy equipped with an energy-dispersive spectrometer. Rockwell C hardness and Vickers microhardness were also measured. Wear behavior in dry conditions was investigated under a load of 300 N using pin-on-disk method. Tribological behavior in boundary lubricated conditions under a load of 60 N at high temperature (100 degrees C) was studied using a custom-made reciprocating tribometer by measuring the mass loss and the friction coefficient. A 5W-40 engine oil was used as lubricant. Atomic force microscopy (AFM) analysis and roughness 2D and 3D of the tested samples were measured. The obtained results showed that in the as-cast state, the added elements favored the formation of simple or complex inter- and intragranular carbides. In the heat-treated state, the microstructure of the examined steels consists of retained austenite, martensite and precipitates. Increasing of heat treatment temperature increases the rate of the formed martensite. Formation of secondary carbides and increasing of martensite amount led to the improvement of hardness and wear resistance.
Keywords: manganese steel; heat treatments temperature; microstructure; wear; friction; BEHAVIOR; Metallurgy & Metallurgical Engineering